Recycling of Portuguese granite quarry fines in geotechnical works: hydraulic and mechanical characterization - Frias, A. (2010)
The fines of two Portuguese granite quarries, located in the Northern region, have been object of a research program aiming its recycling in the construction of transport infrastructures and geotechnical works. In the first phase of this program, a vast number of laboratorial tests were carried out to determine the geoenvironmental and geotechnical properties of these materials. In a second phase, the materials will be used to construct a trial embankment road section. In this paper, the results obtained in the hydraulic and mechanical laboratory tests are presented and discussed. It is concluded that the studied materials show technical viability to be used, in particular, in the construction of embankment transport infrastructures.